PREDIKSI CURAH HUJAN DAN KELEMBABAN UDARA KOTA PEKANBARU MENGGUNAKAN METODE MONTE CARLO - Melani Seprima; Defrianto Defrianto (Komunikasi Fisika Indonesia, 2020)
Weather prediction is important in our lives and can minimize the impact that will occur in the future. Rainfaal and humidity greatly affect the weather conditions in Indonesia. Accuracy in the prediction of rainfall and humidity is very important because it can be used in various interests. The data used are the monthly average data of rainfall and humidity in the city of Pekanbaru in 2014–2018 obtained from BMKG Pekanbaru, then the monthly average data will be processed using a MATLAB R2015a based program so that an average rainfall prediction simulation is obtained and air humidity in 2019–2023. MATLAB R2015a based program using the monte carlo method and has error value 0.0887913.